Comparative infectivity of trachoma organisms in HeLa 229 cells and egg cultures. - Kuo, C C (1975)
Thirty-two trachoma strains were simultaneously titrated in the yolk sac of embryonated chicken eggs and in HeLa 229 cells pretreated with diethylaminoethyl-dextran to determine the relative sensitivity of the two culture systems for detection of the infection. The strains tested were both yolk sac- and HeLa cell-established isolates from the eye and the genital tract. The study showed that the cell culture was of equal or greater sensitivity than yolk sac culture and that ocular and genital isolates differ in their ability to propagate in egg and cell culture: genital strains grow better in cell culture than in eggs and ocular strains grow only slightly better in cell culture.